Variability and Cluster Analysis in Sand Pear (Pyrus Pyrifolia (Burm) Nakai.) Genotypes - Chauhan, Akriti; Singh, Dinesh (Bangladesh Journal of Botany, 2023)
To assess the nature and magnitude of variability in sand pear genotypes of existing plantations a survey was carried out at Solan and Sirmour districts of Himachal Pradesh, India. On the basis of pre selection survey, a total of 92 healthy and bearing sand pear trees were marked during 2018-2021. Wide variation in qualitative and quantitative characters were observed for fruit (physical and biochemical) as well as yield parameters. Range for TSS, titratable acidity, total sugars, reducing sugars, non-reducing sugars, sugar acid ratio, and phenol content was observed as 10.08-18.55°B, 0.12-0.48, 4.95-12.61, 2.95-8.98, 1.01-5.40%, 14.66-68.49 and 1.66-6.40 mg/g, respectively. The cluster dendrogram to elucidate the genetic relationship was performed on the basis of studied parameters to assess pattern of diversity and variability among the accessions. The selected genotypes from existing population excelling in one or more horticultural desirable traits will not only adds to biological diversity but can also be utilized in different breeding programs for development of superior varieties based upon their utility. Bangladesh J. Bot. 52(2): 261-266, 2023 (June)